Sajadah pillow / Nor Asyiqin Nadhirah Roslee Afendi ... [et al.] - Roslee Afendi, Nor Asyiqin Nadhirah; Abu Bakar, Sharifah Hafiza; Ikmal Hisam, Nur Khaleqa Izzah; Md Shahar, Siti Hajar (2021)
This product is called Sajadah Pillow. It is a multi-functional Muslim praying mat that serves as a praying mat as well as a pillow. Pandemic or not, Muslims are obligated to fulfil their five times daily prayers whenever and wherever they are. With the current situation, what was normally provided in the public Muslim prayer room or at the mosque are no longer provided. The product design concept is developed to serve as a convenient yet hygienic carry-on praying mat that could also be used as a pillow for short naps. Physically, the Sajadah Pillow is lightweight and flexible. Storing the product will not post a problem as it can be folded flat into 36cm x 30cm and secure with a buckle. The ultimate design is genuinely clever and utterly convenient even to those using backpacks. Careful consideration was taken in selecting the type of fabric for this product. The nylon fabric will be used for the mat and PVC flocking material for the pillow. These fabrics are lightweight, washable, flexible, and durable and come in various colours and textures. When it is time to use the Sajadah Pillow as a praying mat, all it takes is to release it from the bag, stretch, and flatten it on the floor. To use it as a pillow, transform it by folding the Sajadah into its' bag, fasten it with the zip and blow air through the pin on the corner side of the bag to inflate it. A pillow cover with ripstop nylon is provided to protect the pillow and the Sajadah from dirt, spill, water, and others. In conclusion, the main purpose behind this creative idea is to propose a multi-functional product and useful, especially to accommodate demand from more than one billion Muslim travellers.